Why does risk matter more in recessions than in expansions? - Martin~Møller~ Andreasen; Giovanni Caggiano; Efrem Castelnuovo; Giovanni Pellegrino (Bank of Finland, 2021)
This paper uses a nonlinear vector autoregression and a non-recursive identiÖcation strategy to show that an equal-sized uncertainty shock generates a larger contraction in real activity when growth is low (as in recessions) than when growth is high (as in expansions). An estimated New Keynesian model with recursive preferences and approximated to third order around its risky steady state replicates these state-dependent responses. The key mechanism behind this result is that Örms display a stronger upward nominal pricing bias in recessions than in expansions, because recessions imply higher ináation volatility and higher marginal utility of consumption than expansions.
URN:NBN:fi:bof-202110052045
Keywords: 330; New Keynesian Model; Nonlinear SVAR; Non-recursive identiÖcation; State-dependent uncertainty shock; Risky steady state